ASEAN REGIONAL ARBITRATION BOARD: AN ALTERNATIVE DISPUTE RESOLUTION IN THE ASEAN REGION WITHIN THE FRAMEWORK OF THE ASEAN ECONOMIC COMMUNITY - Dian Maris Rahmah; Tri Handayani (Jurnal Hukum dan Peradilan, 2019)
Transactions among ASEAN member countries are increasingly open with the release of the ASEAN Economic Community (MEA). Entrepreneurs in ASEAN countries are expected to make more transactions with their business partners in the Southeast Asian region. Increasing business relations in the ASEAN region will in part affect the increase in disputes among ASEAN entrepreneurs. This study aims to provide an idea regarding the establishment of the ASEAN Regional Arbitration Agency as an effort to overcome the issue of the execution of arbitration decisions by utilizing regional unification. This research is descriptive analytical using a normative juridical approach. The results of the study show that ASEAN should be a place for resolving international commercial disputes, especially on business transactions carried out in the ASEAN member countries, if ASEAN has a regional arbitration forum, the procedure for resolving business disputes in this region will be simpler, more effective and easier. Legal system barriers can also be overcome if there are procedures that are jointly recognized.